Padrão de uso de recursos alimentares por aves insetívoras de sub-bosque em florestas monodominantes na planície do Pantanal - Gurka, Carlos Augusto Queiroz (2015)
Resource use patterns in natural population, typically variable in morphological, physiological and behavioral characteristics, may be investigated by overlapping diets analysis. Many metrics grant this overlap characterization, among them the network approach is an efficient way used to describe diet overlap between individuals, providing new insights about processes and implications of individual variation. In This study we evaluate pattern of resources use within insectivorous guild understory birds in Cambará (Vochysia divergens Pohl) monospecific forests. The study was conducted in Pirizal region, northern portion of Pantanal wetlands (Mato Grosso, Brazil). For birds sampling, we used mist nets. Considering diet composition, we calculated food niche range for each species and each population using Shannon diversity index. To calculate Inter-individual diet variation we use E index, based on a network approach, subsequently, checked if there is correlation with niche variation range by using simple linear regression. The nested level, ecological pattern reported for diet interspecific interactions networks of species was estimated by NODF metric and in addition, we identified modular structure with QuanBiMo algorithm (Q), which builds one dendrogram of interacting species, so that most closely related species are prone to interactions.186 individuals were registered in homogeneous formations, distributed in 10 families. Results of niche breadth calculation indicated birds in each species using a significantly smaller set of resources than used by populations. The individual specialization in this guild had positive relationship with niche amplitude increases. Nestedness was not a recurring pattern in this guild that demonstrated through Q modularity test, species groups tending to interact exclusively with certain resources categories, highlighting five groups or modules. Changes in individual characteristics can be decisive when using different resources in each species; it’s believed this kind of change results from populational expansion niche probably caused by mechanisms such as competition. Nesting pattern and modularity calculation are metrics that provide formal description of functional aggregation populations, identifying potentially critical scale for ecological and evolutional dynamics of species.